Um estudo sobre a política de combate às drogas sob o enfoque da criminologia crítica - Pinto, Luiz Antônio Francisco (Universidade Federal do Tocantins, 2017)
This text brings in the discussion about the drug dealing combat policy in Brazil, under the emphasis of Criticism Criminology. The work is based on authors like Alessandro Baratta and Salo de Carvalho. The argumentation goes on questioning prohibitionism, witch is the bases of the combat policies over the entire world, including Brazil. Under a historical point of view, it´s obvious that prohibiotionism hasn´t been effective in avoiding drug consumption growth, let alone minimizing the deleterious effects over the social issue generated by the drug market, involving in itself a great amount of crimes that affect all the society, in special, the working masses with low incomes.Under this radar, the current combat policy, while not sorting out drug dealers from consumers, contributes itself for the prision population growth. In Brazil particularly, this phenom hurts Human Rights. The Marijuana regulamentation, in this direction, might be a strong factor to avoid the arrest of young users caught with a small amount of the drug. While the decriminalization is still on debate, the government can face the problem with paleactive procedures that would help justice, like Restaurative Justice, Therapeutic Justice and the Custody Audience, for instance. All of them alternatives for the arrest. Lastly, this study brings some theorical insights over the Damage Reduction Policy, a global tendency adopted by many countries that has joined the idea of drug discriminalization.